16
$\begingroup$

Given $x,y,z\geq0$ and $xy+yz+zx=1$. Show that $\displaystyle\frac 1 {\sqrt{x+y}}+\frac 1 {\sqrt{y+z}}+\frac 1 {\sqrt{z+x}}\geq2+\frac 1 {\sqrt2}$.

I've tried many things but all failed. The only thing I know is that the equality holds when $x=y=1, z=0$.

Please help. Thank you.

$\endgroup$
  • 1
    $\begingroup$ I think there would be $x=y=1, z=0$ for equality. $\endgroup$ – Mher Jun 7 '13 at 9:33
  • 1
    $\begingroup$ There is such identity. $cot(a)cot(b)+cot(b)cot(c)+cot(c)cot(a),$ if $a+b+c=\pi.$ Try substitution $x=a, y=b, z=c.$ $\endgroup$ – Mher Jun 7 '13 at 9:54
  • $\begingroup$ I'm not good at these things, but maybe it's an application of Muirhead's inequality? $\endgroup$ – Daniel McLaury Jun 7 '13 at 11:01
2
$\begingroup$

Without loss of generality, we assume that $x\ge y\ge z$.

Lemma 1: $$\dfrac{1}{\sqrt{y^2+1}}+\dfrac{1}{\sqrt{z^2+1}}\ge 1+\dfrac{1}{\sqrt{(y+z)^2+1}}$$

Proof: this inequality is equivalent to $$\dfrac{1}{y^2+1}+\dfrac{1}{z^2+1}+\dfrac{2}{\sqrt{(y^2+1)(z^2+1)}}\ge 1+\dfrac{1}{(y+z)^2+1}+\dfrac{2}{\sqrt{(y+z)^2+1}}.$$ Notice that $$(y+z)^2+1-(y^2+1)(z^2+1)=yz(2-yz)\ge 0,$$ hence $$\dfrac{2}{\sqrt{(y^2+1)(z^2+1)}}\ge\dfrac{2}{\sqrt{(y+z)^2+1}}.$$ Therefore, it suffices to prove that $$\dfrac{1}{y^2+1}+\dfrac{1}{z^2+1}\ge1+\dfrac{1}{(y+z)^2+1}.$$ And this is equivalent to $$\dfrac{yz[2-2yz-yz(y+z)^2]}{(y^2+1)(z^2+1)[(y+z)^2+1]}\ge 0.$$ Above is true because $$2-2yz-yz(y+z)^2=2x(y+z)-yz(y+z)^2=(y+z)[2x-yz(y+z)]\ge (y+z)[2x-x^2(y+z)]=x(y+z)(2-xy-xz)\ge 0.$$


Lemma 2: $$\dfrac{1}{x+y}+\dfrac{1}{\sqrt{x+z}}\ge\sqrt{y+z}+\sqrt{\dfrac{y+z}{(y+z)^2+1}}.$$

Proof: \begin{align}\dfrac{1}{x+y}+\dfrac{1}{\sqrt{x+z}}&=\sqrt{y+z}\left(\dfrac{1}{\sqrt{(y+z)(x+y)}}+\dfrac{1}{\sqrt{(z+x)(z+y)}}\right)\\ &=\sqrt{y+z}\left(\dfrac{1}{\sqrt{1+y^2}}+\dfrac{1}{\sqrt{1+z^2}}\right) \end{align} and apply Lemma 1, then done!


Thus the original inequality is equivalent to $$\dfrac{1}{\sqrt{y+z}}+\sqrt{y+z}+\sqrt{\dfrac{y+z}{(y+z)^2+1}}\ge 2+\dfrac{1}{\sqrt{2}}.$$

Letting $$t=\dfrac{1}{\sqrt{y+z}}+\sqrt{y+z}\ge 2,$$ the inequality becomes $$t+\dfrac{1}{\sqrt{t^2-2}}\ge 2+\dfrac{1}{\sqrt{2}}.$$

This can be shown by the following: \begin{align} &t+\dfrac{1}{\sqrt{t^2-2}}-2-\dfrac{1}{\sqrt{2}} \\ =&t+\dfrac{2\sqrt{2}}{2\sqrt{2}\cdot\sqrt{t^2-2}}-2-\dfrac{1}{\sqrt{2}} \\ \ge& t+\dfrac{2\sqrt{2}}{2+t^2-2}-2-\dfrac{1}{\sqrt{2}} \\ =&t+\dfrac{2\sqrt{2}}{t^2}-2-\dfrac{1}{\sqrt{2}} \\ =&\dfrac{(t-2)(\sqrt{2}t^2-t-2)}{\sqrt{2}t^2}\ge 0. \end{align}

| cite | improve this answer | |
$\endgroup$
  • $\begingroup$ I edited the format and some phrases. +1 $\endgroup$ – Shuhao Cao Jun 19 '13 at 14:47
2
$\begingroup$

$z=\dfrac{1-xy}{x+y} \ge 0 \to xy\le 1$

LHS$=\sqrt{\dfrac{1}{x+y}}+\sqrt{\dfrac{x+y}{1+x^2}}+\sqrt{\dfrac{x+y}{1+y^2}}=f(x,y)$

$f'_{x}=\dfrac{1-x^2-2xy}{(x^2+1) \sqrt{x^2+1} \sqrt{x+y}}+\dfrac{1}{\sqrt{(x+y)(y^2+1)}}-\dfrac{1}{(x+y)\sqrt{x+y}}=0$......<1>

$f'_{y}=\dfrac{1-y^2-2xy}{(y^2+1) \sqrt{y^2+1} \sqrt{x+y}}+\dfrac{1}{\sqrt{(x+y)(x^2+1)}}-\dfrac{1}{(x+y)\sqrt{x+y}}=0$......<2>

<1>$*(1+y^2)$-<2>$*(1+x^2)$:

$(y^2-x^2)\left(2(x+y)(1-xy)+\dfrac{(1+x^2)(1+y^2)}{\sqrt{1+x^2}{1+y^2}}\right)=0$

so we have $x=y$ only. put in <1>, we get: $4x-4x^3=(x^2+1)^{\frac{3}{2}}$,ie:

$15x^6-35x^4+13x^2-1=0 \to (3x^2-1)(5x^4-10x^2+1)=0$, we get two roots:

$x_1=\dfrac{1}{\sqrt{3}}, x_2=\sqrt{1-\dfrac{2}{\sqrt{5}}}$

$f(x_1)=2.79,f(x_2)=2.77$,but we note $f(x,y)$ when $x ,y \to \infty, f(x,y) \to 0$,so we have to check the bound, which is $xy=1$.

$f(x,y)=\sqrt{x}+\dfrac{1}{\sqrt{x}}+\dfrac{1}{\sqrt{\dfrac{1}{x}+x}}$

let $m=\sqrt{x}+\dfrac{1}{\sqrt{x}} \ge2$

$f(m)=m+\dfrac{1}{\sqrt{m^2-2}}$, when $m\ge 2$, $f(m)$ is mono increasing, so the minimum will be got when $m=2 \to x=y=1, f(1)=2+\dfrac{1}{\sqrt{2}}< 2.77$, so the minimum is $2+\dfrac{1}{\sqrt{2}}$.

To prove $f(m)=m+\dfrac{1}{\sqrt{m^2-2}}$ is mono increasing function,

$f'(m)=1-\dfrac{m}{(m^2-2)^{3/2}}=1-\dfrac{1}{\sqrt{m^2-2}\left(m-\dfrac{2}{m}\right)}>0$ when $m\ge 2$.

| cite | improve this answer | |
$\endgroup$
  • $\begingroup$ Why are you able to restrict $z$ as $f(x, y)$ in the beginning? I thought $z$ was an independent variable $\endgroup$ – Ovi Jun 9 '13 at 19:43
  • $\begingroup$ I am not restrict z, it is just same function. you can use Lagrange multiplier to get same roots but it is very hard, especially for last root (1,1,0).it is mess. $\endgroup$ – chenbai Jun 10 '13 at 2:44

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.